(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
Globalization, which is transforming the world into a unified system through economic, cultural, political, and social dimensions, significantly influences the processes of education and upbringing. These include not only issues of the revision of curricula and the change in teaching methods, but also the ones related to public thinking, cultural expression, and social cohesion. The impact of globalization on the educational-upbringing process becomes particularly evident as the interaction and exchange of diverse cultures and values can lead to the loss or transformation of cultural identity and national values. This article presents findings from a study focused on the impact of globalization on the organization of educational-upbringing processes in public educational institutions—particularly in the context of national identity, cultural values, and the transformation of pedagogical methods. It explores how teachers perceive globalization, how they respond to the associated challenges, and what changes they observe in their professional activities. The article is based on survey results collected from teachers working in public schools. The relevance of this research stems from ongoing changes in the field of education, the development and integration of educational technologies, and growing concerns regarding the preservation of national identity. The scientific novelty of the article lies in its historical and comparative analysis of globalization, supported by data gathered through surveys conducted among teachers. The article discusses both theoretical and practical approaches that can help preserve national identity while effectively responding to global educational trends. The analysis reveals that a significant number of teachers perceive globalization as a threat to national identity, yet at the same time recognize its positive contributions to technological, scientific, and professional advancement. The article proposes a combined approach that emphasizes the preservation of cultural identity, modernization of educational methods, and continuous professional development of teachers in response to global challenges.